Utilization of Visual Media in Arabic Teaching - Rahmad, Muhammad; Joe , Alex; Ino , Reiza (Journal International of Lingua and Technology, 2022)
Learning media is needed by teachers to help a teaching in education. This discussion intends to determine the use of media in learning Arabic. In addition to using books or lecture methods, media is also a tool used in teaching and teachers are also expected to have different learning media and according to the material and circumstances of each student. Everyone is relied on to understand technology as a support for all existing activities, as well as in the realm of education because considering the increasingly rapid and advanced technological developments. Teachers and students can take advantage of technology-based learning media, including the Canva application. Canva is an online-based design application that provides all the attractive designs such as templates, features, and categories that we can use in it. By utilizing the Canva application, teachers can show information, innovations, and abilities that will be obtained by students by utilizing attractive designs in the Canva application, so that this media can support the learning process so that it is not boring and can also be used in various areas of life. So with this learning media, the interest of students will increase in learning and help teachers to motivate students towards more enjoyable learning. With the existence of learning media, the learning process will be much more efficient and increase students' insight into learning through information and communication technology.